2022
DOI: 10.1155/2022/3541931
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Analysis of Clinical Effects of Insulin Aspart Combined with Acarbose and Metformin in the Treatment of Diabetes Mellitus

Abstract: Objective. To investigate the clinical effect of Insulin aspart 30 combined with acarbose and metformin enteric-coated tablets in the treatment of diabetes mellitus. Methods. 90 diabetic patients admitted to our hospital from January 2019 to December 2021 were selected as the research subjects, and the patients were randomly divided into group A (n = 30, using insulin aspart 30 alone), group B (n = 30, using insulin aspart 30 combined with metformin enteric-coated tablets), and group C (n = 30, using insulin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%